2022
DOI: 10.1111/sms.14270
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the COVID‐19 pandemic by Paralympic athletes preparing for elite sport events: A longitudinal study

Abstract: Introduction This study investigates the impact of the COVID‐19 pandemic on mental health, coping styles and their relationship, and training opportunities in elite athletes with disabilities (AwD) preparing for national and international sport events during a ten‐month observation period. Methods The study covered four time points in 3‐month intervals, one retrospective, and three times during the 10 months of the pandemic period with diversified numbers of average new infections per day: A—pre‐pandemic, B—th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…In summary, similar to other findings conducted during the pandemic on the general population [31,32], our study confirmed that the EO coping style negatively affects components of mental health such as loneliness. This contrasts with research showing that coping styles did not significantly predict other mental health dimensions such as anxiety and depression over time [17]. Specifically, the styles used in the initial phase of the pandemic did not predict anxiety and depression levels measured 3 months later.…”
Section: Variablescontrasting
confidence: 91%
See 1 more Smart Citation
“…In summary, similar to other findings conducted during the pandemic on the general population [31,32], our study confirmed that the EO coping style negatively affects components of mental health such as loneliness. This contrasts with research showing that coping styles did not significantly predict other mental health dimensions such as anxiety and depression over time [17]. Specifically, the styles used in the initial phase of the pandemic did not predict anxiety and depression levels measured 3 months later.…”
Section: Variablescontrasting
confidence: 91%
“…Despite athletes being considered individuals with higher extraversion, greater emotional stability, and a stronger sense of responsibility than nonathletes, potentially making them better equipped to handle difficulties [15,16], the pandemic posed a unique challenge affecting their functioning [11,17]. Therefore, the aim of the current study was to assess AWD's experiences of loneliness during the pandemic periods, as well as to assess the relationship between loneliness, coping styles and demographic factors (age, gender), disability-related factors (type of disability, time since injury), and sport-specific factors (sport discipline, athletic tenure) within this population.…”
Section: Introductionmentioning
confidence: 99%
“…Para-athletes with lower recovery levels, which are associated with low functionality, may present with a lack of interest in sport, such as in maintaining fitness for the next competition. In addition, the uncertainties of the COVID-19 pandemic could have aggravated such conditions because of the need to adapt to sanitary measures [26,27].…”
Section: Dashmentioning
confidence: 99%
“…Although athletes with disabilities reported less distress during the pandemic than able-bodied athletes in one study ( Fiorilli et al, 2021 ), persons with disabilities reported experiencing greater pandemic-related stress than persons without disabilities in the general population, and Paralympic athletes reported lower levels of mental health than a sample matched on age and gender from the general population ( Busch et al, 2022 ) in other studies. Moreover, given the uniqueness of the circumstances, it is possible that the item content on standardized coping inventories may not fully capture the range of coping activities with which people engage and that responses to such inventories may not reflect what people do when confronted by the set of stressors characteristic of the COVID-19 pandemic ( Urbański et al, 2023 ). It is, therefore, necessary to consider pandemic-specific coping efforts when investigating the association between coping and mental health outcomes during the pandemic.…”
Section: Introductionmentioning
confidence: 99%